Implementation of Monitoring and Evaluation of Teacher Performance at Madrasah Aliyah Salafiyah Darul Muta’allimin Tanah Merah Aceh Singkil - Miranti Adelia Afda; Fachruddin Fachruddin; Makmur Syukri (Edumaspul: Jurnal Pendidikan, 2022)
Implementation of monitoring and evaluation of teacher performance, namely providing an assessment of the programs implemented by the teacher in accordance with the plans made and identifying problems that arise in the implementation of school programs so that they can be overcome. At Madrasah Aliyah Salafiyah Darul Muta'allimin Tanah Merah Aceh Singkil there are several phenomena that seem related to the low performance of teachers including; (1) teachers carry out teaching and learning activities not in accordance with a predetermined time allocation, (2) there are still some teachers who make teaching only an obligation without thinking about the interests of the students and the interests of the madrasah, (3) there is a lack of teacher initiative in the form of creativity in activities learning, (4) some teachers prioritize personal interests over the interests of the madrasah. The purpose of this study was to find out implementation, implementation techniques, and constraints in monitoring and evaluating teacher performance at Madrasah Aliyah Salafiyah Darul Muta'allimin Tanah Merah Aceh Singkil. This study uses a qualitative descriptive research method with data collection techniques using observation and interviews. The results of this study indicate that the implementation of monev on teacher performance at Madrasah Aliyah Salafiyah Darul Muta'allimin Tanah Merah has been going well, starting with monev planning by conducting discussions involving teachers by making various considerations so that the implementation of teacher performance monitoring and evaluation runs effectively and efficiently, using various implementation techniques and combining the results, evaluating the program to find out how far the program has been running and reducing the impact of losses from its implementation and improving teacher performance in the future. There are three types of monev implementation techniques for teacher performance at Madrasah Aliyah Salafiyah Darul Muta'allimin Tanah Merah; (1) Observation, that is, the head of the madrasa makes direct visits so that the activities is in progress or the object you want to observe can be seen, (2) Interview, namely the principal conducts monitoring aimed at one person by conducting direct question and answer, (3) FGD, namely monitoring through the process of solving a problem by unifying equations thoughts and addressing the matters referred to that have been mutually agreed upon through group discussions. obstacles in the process of implementing monev at Madrasah Aliyah Salafiyah Darul Muta'allimin Tanah Merah, namely first, there is no schedule allocated for the implementation of monev so that the initiatives taken to cover these obstacles are deliberations and meetings held during breaks, as well as at the end of class.